Calcium partially relieves the deleterius effects of hypoxia on a maize cultivar selected for waterlogging tolerance (2005)
Low soil oxygen concentrations due to waterlogging or transient flooding severely reduce maize production. However, genotypes with tolerance or even resistance to hypoxia develop morphological and biochemical adaptation mechanisms which may prove to be useful criteria for the selection and breeding of new improved genotypes. The objective of this work was to evaluate the effect of levels and modes of application of calcium sources on biomass yield, the contents of total soluble sugars and reduced sugars and on the activities of invertase isoforms and phosphoenolpyruvate carboxylase, in a maize variety (BRS 4154) derived from the 14th selection cycle for tolerance to transient soil flooding conditions, when cultivated under waterlogging conditions. The study was carried out in a greenhouse, utilizing 20 kg pots, filled with a lowland soil. The effects of two sources of calcium (CaCl2 , 300 kg ha-1 and CaSO4 , 500 and 1.500 kg ha-1) and three modes of application (applied 8 cm below surface, mixed with the whole soil volume and surface application) were tested in soils kept at field capacity and waterlogged after plants reached growth stage V6. Above ground biomass yield, the contents of total soluble sugars and reducing sugars and the activities of the neutral citosol (INC), acid vacuolar (IAV), acid cell wall invertases and phosphoenolpyruvate carboxylase were determined at the onset of flowering. Calcium application partially relieved the deleterious effect of waterlogging on biomass yield and the activities of INC, IAPC and PEPcase.